Dynamics of work limitation and work in Australia - Umut Oguzoglu (Institute for the Study of Labor (IZA), 2007)
This paper examines the impact of self-reported work limitation on the labour force participation of the Australian working age population. Five consecutive waves of the Household, Income and Labour Dynamics in Australia (HILDA) Survey are used to investigate this relationship. A two-equation dynamic panel data model demonstrates that persistence and unobserved heterogeneity play an important role in the work limitation reporting and its effect on labour force participation. Unobserved factors that jointly drive work limitation and participation are also shown to be crucial, especially for women.
Keywords: 330; Behinderte Arbeitskräfte; Beschäftigung; Australien